2017
DOI: 10.1155/2017/2571630
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Challenges of a Primary Vertebral Artery Aneurysm Causing Recurrent Ischemic Strokes

Abstract: Background. Extracranial vertebral artery aneurysms are a rare cause of embolic stroke; surgical and endovascular therapy options are debated and long-term complication may occur. Case Report. A 53-year-old man affected by neurofibromatosis type 1 (NF1) came to our attention for recurrent vertebrobasilar embolic strokes, caused by a primary giant, partially thrombosed, fusiform aneurysm of the left extracranial vertebral artery. The aneurysm was treated by endovascular approach through deposition of Guglielmi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Strambo et al reported that proximal occlusion was implemented for vertebrobasilar embolic strokes caused by a primary, partially thrombosed, giant fusiform aneurysm of the left extracranial VA, but six years later, the result was stroke recurrence because the aneurysm had been revascularized from its distal portion by reverse blood flow coming from the patent vertebrobasilar axis. 31) Furthermore, following treatment with proximal occlusion with a detachable balloon, a vertebral arteriovenous fistula developed in the same region 11 years later. 17) These might be therapeutic pitfalls of proximal occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Strambo et al reported that proximal occlusion was implemented for vertebrobasilar embolic strokes caused by a primary, partially thrombosed, giant fusiform aneurysm of the left extracranial VA, but six years later, the result was stroke recurrence because the aneurysm had been revascularized from its distal portion by reverse blood flow coming from the patent vertebrobasilar axis. 31) Furthermore, following treatment with proximal occlusion with a detachable balloon, a vertebral arteriovenous fistula developed in the same region 11 years later. 17) These might be therapeutic pitfalls of proximal occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…and interventional embolization (balloons, coils, tissue glue, vinyl alcohol polymers, etc.) (25)(26)(27)(28)(29)(30). However, whether it is traditional open surgery or interventional embolization, vascular fragility associated with NF-1 brings great risk to treatment, viz., rupture of blood vessels and bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…CT angiography and DSA are the standard tools to diagnose and reveal the anatomy of vasculature and to plan treatment. Treatment options include ligation, isolation, balloon embolisation, onyx embolisation and coil embolisation 6 9–11. There is no single standardised treatment option for V1-segment vertebral artery aneurysms with a fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Both surgical and endovascular treatments carry potential risks and technical difficulties. The best treatment options are still controversial in such aneurysms 3–6. Here we present a case of a successfully treated ruptured dissecting V1 vertebral artery aneurysm making a fistula with the adjacent vein using endovascular coils and placement of a distal plug to close the fistula and proximally occlude the parent artery.…”
Section: Introductionmentioning
confidence: 97%